Modelling the relative abundance of the primary African vectors of malaria before and after the implementation of indoor, insecticide-based vector control. (December 2016) - Sinka, Marianne; Golding, Nick; Massey, N.; Wiebe, Antoinette; Huang, Zhi; Hay, Simon; Moyes, Catherine
Abstract Background Malaria remains a heavy burden across sub-Saharan Africa where transmission is maintained by some of the world's most efficient vectors. Indoor insecticide-based control measures have significantly reduced transmission, yet elimination remains a distant target. Knowing the relative abundance of the primary vector species can provide transmission models with much needed information to guide targeted control measures. Moreover, understanding how existing interventions are impacting on these relative abundances highlights where alternative control (e.g., larval source management) is needed. Methods Using the habitat suitability probabilities generated by predictive species distribution models combined with data collated from the literature, a multinomial generalized additive model was applied to produce relative abundance estimates forAnopheles arabiensis, Anopheles funestus andAnopheles gambiae/Anopheles coluzzii . Using pre- and post-intervention abundance data, estimates of the effect of indoor insecticide-based interventions on these relative abundances were made and are illustrated in post-intervention maps. Results Conditional effect plots and relative abundance maps illustrate the individual species' predicted habitat suitability and how they interact when in sympatry.Anopheles arabiensis andAn. funestus show an affinity in habitat preference at the expense ofAn. gambiae /An. coluzzii, whereas increasing habitat suitability forAn. gambiae /An. coluzzii is conversely less suitable forAn. arabiensis but has little effect onAn. funestus. Indoor insecticide-based interventions had a negative impact on the relative abundance ofAn. funestus, and a lesser effect onAn. arabiensis . Indoor residual spraying had the greatest impact on the relative abundance ofAn. funestus, and a lesser effect onAn. gambiae /An. coluzzii . Insecticide-treated bed nets reduced the relative abundance of both species equally. These results do not indicate changes in the absolute abundance of these species, which may be reduced for all species overall. Conclusions The maps presented here highlight the interactions between the primary vector species in sub-Saharan Africa and demonstrate thatAn. funestus is more susceptible to certain indoor-based insecticide interventions thanAn. gambiae /An. coluzzii, which in turn, is more susceptible thanAn. arabiensis . This may provideAn. arabiensis with a competitive advantage where it is found in sympatry with other more endophilic vectors, and potentially increase the need for outdoor-based vector interventions to deal with any residual transmission barring the way to malaria elimination.